Molecular dynamics simulation of solidification kinetics of aluminium using Sutton-Chen version of EAM - Ozgen, S; Duruk, E (Elsevier Science Bv, 2004)
In recent years, it has been found out that the metals and alloys produced by rapid cooling techniques have more superior and surprising features upon electricity and magnetism than the crystal-structured systems. In this study, aluminium is modelled by using Sutton-Chen version of embedded atom method (EAM) including many body interactions. Amorphous and crystal structures of aluminium are reproduced by applying fast cooling and slow cooling treatments, respectively, by means of molecular dynamics (MD) simulations, and their structural properties are examined. During slow cooling process applied continuously, not gradually, it has been observed that the system has a state of energetically unfavourable complex arrangement in cluster level at a temperature above glassy transition temperature. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: molecular dynamics simulation; embedded atom method; amorphous phases; solidification